2014
DOI: 10.1002/hec.3128
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Declining Rates in a Per Diem Payment System

Abstract: The paper demonstrates differential effects of a prospective payment system with declining per diem rates, dependent on the percentiles of length of stay. The analysis uses dynamic panel data estimates and a recent nationwide administrative database for major diagnostic categories in 1068 Japanese hospitals in 2006-2012 to show that average length of stay significantly increases for hospitals in percentiles 0-25 of the pre-reform length of stay and significantly decreases for hospitals in percentiles 51-100. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Fourth, our results may not be generalizable to conditions with short or very long average LOS. Other studies suggest that financial incentives may have differential effects on discharge behaviour over LOS [8,16]. However, as we provide evidence on marginal reimbursement incentives manifesting at an LOS of 10-22, depending on the cost group, we are only able to draw conclusions about this treatment duration.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Fourth, our results may not be generalizable to conditions with short or very long average LOS. Other studies suggest that financial incentives may have differential effects on discharge behaviour over LOS [8,16]. However, as we provide evidence on marginal reimbursement incentives manifesting at an LOS of 10-22, depending on the cost group, we are only able to draw conclusions about this treatment duration.…”
Section: Discussionmentioning
confidence: 55%
“…days 10-22, depending on the cost group (see Table 1), of the LOS distribution. Evidence suggests that financial incentives may have a differential effect over LOS [8,16]. Furthermore, Pletscher [17] investigated a mixed reimbursement system consisting of per diem rates and case payment depending on the timing of discharge, which might lead to stronger financial incentives compared to solely declining per diem reimbursement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These reductions in inpatient LOS across health systems have been a result of a number of different factors. Within acute hospitals, greater use of more efficient surgery (Downing et al, 2009;Jayne et al, 2010;Laudicella et al, 2016), better discharge planning (Dedhia et al, 2009;Siegler et al, 2013), increasing use of palliative care planning (Brody et al, 2010), reductions in delayed discharges (McCoy et al, 2007;Rae et al, 2007) and more efficient payment mechanisms (Besstremyannaya, 2016;Borghans et al, 2008;Échevin and Fortin, 2014;Farrar et al, 2009) have been shown to reduce LOS. For specific patient populations, focused care units such as early supported discharge units and stroke units (Confalonieri et al, 2015;Keegan and Smith, 2013) and greater provision of non-acute follow-up and rehabilitation care have also been shown to allow patients to be discharged more quickly to potentially more appropriate care settings (Dahl et al, 2015;Gozalo et al, 2015;McCoy et al, 2007;Neiterman et al, 2015;Wren et al, 2014).…”
Section: Acute Capacity and Length Of Staymentioning
confidence: 99%
“…These reductions in inpatient length of stay are due to several factors. Within hospitals, greater use of more efficient surgery [ 2 – 4 ], better discharge planning [ 5 , 6 ], palliative care planning [ 7 ], reductions in delayed discharges [ 8 , 9 ], and more efficient payment mechanisms [ 10 13 ] have been shown to reduce length of stay. For specific patient populations, focused care units, such as for early supported discharge units and stroke units [ 14 , 15 ], and greater provision of non-acute follow-up and rehabilitation care [ 8 , 16 18 ] has allowed patients to be discharged more quickly.…”
Section: Introductionmentioning
confidence: 99%